Evaluation of QuantiFERON tuberculosis Gold In‐Tube assay for diagnosis of active tuberculosis in children. (12th November 2019) - Zubarioglu, Tanyel; Bayraktar, Banu; Dalgic, Nazan; Sancar, Mesut; Cakir, Erkan; Togay, Alper; Gencer, Hasim; Bulut, Emin; Yalciner, Altan
Abstract : Aim: Tuberculin skin test (TST) is still used in diagnostic algorithms of childhood tuberculosis (TB). QuantiFERON TB Gold In‐Tube assay (QFT‐GIT) is an alternative test to TST based on the detection of interferon‐gamma release upon in vitro induction of peripheral mononuclear cells by TB antigens. In this study, we aimed to determine the diagnostic value and performance of QFT‐GIT for active childhood TB. Methods: This retrospective study was conducted between January 2005 and December 2011 in three referral hospitals in Turkey with 124 children who were diagnosed with definite active TB. Sensitivity values of TST and QFT‐GIT were determined by accepting the microbiological confirmation as the gold standard of diagnosis of TB. Results: In our study, sensitivity of QFT‐GIT and TST was found to be 65 and 66% respectively. However, combined usage of QFT‐GIT and TST was found to be more sensitive (85%) than TST or QFT‐GIT alone ( P  < 0.0001). Although negative results of QFT‐GIT or TST did not exclude the diagnosis of active TB in children, their positivity supported the diagnosis. Specificity could not be measured as only microbiologically confirmed cases of Mycobacterium tuberculosis disease were enrolled in the study. Conclusion: Although sensitivities of TST and QFT‐GIT are too low to exclude active TB, their positivity supports diagnosis of active TB in children concomitant with signs and symptoms. QFT‐GIT and TST should be used together to enhance diagnostic sensitivity and could help exclude a diagnosis of TB if the pretest probability is low.